Reconceptualizating impunity in cases of gender violence in Mexico - Pamela Teutli (Oñati Socio-Legal Series)
The increase of violence against women and girls (VAWG) in Mexico, in its various contexts and modalities comes hand in hand with a perception of impunity that calls into question the effectiveness of the criminal justice system to attend this problem. The creation of new crime regulations and the increase in penalties have proven to be ineffective strategies in the prevention and attention of these cases, since they lack a systemic vision of the problem. This paper seeks to develop an idea of impunity that goes beyond the absence of punishment and is defined on the basis of the structural notion of VAWG. Therefore, impunity can be associated with the absence of access to justice and a gender perspective.